Orthogonal decision-feedback detector for asynchronous multiuser CDMA systems. - Hsiao-Hwa Chen (IEEE Transactions on communications)
This paper introduces an asynchronous orthogonal decision-feedback detector (AODFD) for asynchronous CDMA multiuser detection. The AODFD based on entire message-length detection is studied first. A realizable scheme, sliding-window AODFD, is then proposed and its performance is analyzed. In spite of its simple structure, the sliding-window AODFD can perform as desirably as ADDFD, which has a much higher complexity. The reduced complexity of the sliding-window AODFD is due to the use of orthogonal matched-filtering and a short window size. Different from ADDFD that requires computational intensive z-transformed matrix inversion and spectral factorization, AODFD uses the agile Gram-Schmidt procedure. It is possible for AODFD to adopt a simple updating algorithm and parameter updating is no longer always necessary when users leave the system. The comparisons are also made with other orthogonal-based detectors and the bit error probability results show that the AODFD is an attractive multiuser detector